2007
DOI: 10.1097/01.rct.0000243455.23308.a9
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Features of Pulmonary Septic Emboli

Abstract: The detailed CT characteristics of peripheral nodules in pulmonary septic emboli may be able to differentiate the causative microorganisms and to provide additional information regarding treatment plans in patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…3D). Furthermore, cavitation within nodules is commonly observed in patients with Gram-positive septic emboli (9). In the current case, CT findings, including bilateral nodular opacity with cavitation, right pleural effusion and mediastinal lymphadenopathy, were consistent with those observed in cases of SPE (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…3D). Furthermore, cavitation within nodules is commonly observed in patients with Gram-positive septic emboli (9). In the current case, CT findings, including bilateral nodular opacity with cavitation, right pleural effusion and mediastinal lymphadenopathy, were consistent with those observed in cases of SPE (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…In the present case, however, no pathogens were detected in the blood or removed catheter. Commonly accepted principles for the treatment of SPE include the prompt empiric administration of intravenous antibiotics (8), the detection and removal of any potentially infected devices and surgical intervention to remove the collection purulent fluid (9). We herein report a rare case of SPE caused by infection-associated catheter removal in a patient with Hodgkin's lymphoma.…”
Section: Introductionmentioning
confidence: 97%
“…It is noteworthy that KWON et al [185] recently reported that the size of the nodules in gram-positive septic emboli was larger than those in gram-negative. Cavitation and air bronchogram within the nodules were seen more frequently in the grampositive emboli, while a ground-glass attenuation halo around a nodule and a feeding vessel sign were more commonly observed in gram-negative emboli.…”
Section: Diagnosismentioning
confidence: 99%
“…A thrombus containing microorganisms embedded in fibrin mobilised from an infectious nidus is implanted in the pulmonary arteries, leading to an infarction inciting a metastatic abscess ( fig. 3a) [176,185]. Cavitary parenchymal nodules may be caused by septic occlusion of small peripheral PA branches [186].…”
Section: Pathophysiologymentioning
confidence: 99%
“…This sign may represent hematogenous spread to the lungs and may also be seen in metastasis. The prevalence of this sign varies from 67-100% in various series and the heterogeneous sub pleural wedge-shaped opacities are seen in 70-75% of patients (Kwon et al, 2007). Multi-detector CT is faster and superior to the classical CT technology for detection of this sign (Dodd et al, 2006).…”
Section: Diagnosismentioning
confidence: 99%